Preparation, thermal characterization and examination of phase change materials (PCMs) enhanced by carbon-based nanoparticles for solar thermal energy storage. (October 2019) - He, Meizhi; Yang, Luwei; Lin, Wenye; Chen, Jiaxiang; Mao, Xiang; Ma, Zhenjun
Highlights: An experimental framework for NePCMs development was proposed and utilised. GNPs outperformed MWCNTs and NG on thermal conductivity enhancement of NePCMs. Adding 3 wt% of GNPs into myristic acid enhanced the thermal conductivity by 176.26%. Nano-additives reduced phase change temperature range and super-cooling of the PCM. The NePCMs developed showed good stability and bulk phase change performance. Abstract: This paper presents the preparation and thermal characterization of phase change materials (PCMs) enhanced by carbon-based nanoparticles, including graphene nanoplatelets (GNPs), multi-walled carbon nanotubes (MWCNTs) and nano-graphite (NG). A systematic experimental framework, consisting of material selection and preparation, material property characterization and thermal performance examination, was proposed and used in this study to facilitate the development of nano-enhanced PCMs (NePCMs) for solar thermal energy storage applications. By applying this framework, the characteristics and potential performance of PCM composites can be comprehensively understood, and better assessed before practical applications. It was found that the thermal conductivity of the myristic acid (MA) can be significantly enhanced by adding the nanoparticles in particular GNPs as additives into the PCM. The thermal conductivity of the PCM composites can be improved by 176.26%, 47.30% and 44.01% respectively under the solid phase, by adding GNPs, MWCNTs and NG with a concentration of 3 wt%. However, the concentration of the nanoparticles needs to be carefully determined to maximise the benefit in thermal conductivity enhancement. Different from that under the solid phase, the thermal conductivity enhancement of the NePCMs developed under the liquid phase followed linear increasing trends with relatively low increasing rates, when increasing the concentration of the nanoparticles. Besides the thermal conductivity enhancement, the adding of nanoparticles also modified the phase change process with a smaller phase change temperature range and eliminated supercooling while maintaining the high latent heat capacity. A further thermal performance examination demonstrated that the prepared NePCMs showed high thermal and chemical stability, which can be used to substantially reduce the phase transition time, and therefore are good potential candidates for solar thermal energy storage applications.